A Monte Carlo implementation of the BDMPS-Z formalism - Wiedemann, Urs Achim; Zapp, Korinna Christine; Stachel, Johanna (Nuclear physics. A, Nuclear and hadronic physics, 2011)
We present preliminary results of a Monte Carlo algorithm that provides a faithful representation of the BDMPS-Z formalism for highly energetic partons interacting in dense QCD matter. In the incoherent limit, the evolution is governed by the probabilities for elastic and inelastic scattering of the highly energetic parton with target constituents in the dense QCD matter. A dynamically evolving formation time encodes coherence effects in such a way that a probabilistic implementation of the BDMPS-Z formalism is obtained. Since the scattering probabilities of the proposed algorithm depend on the total elastic and inelastic cross sections presented by target constituents, they will be sensitive to the IR and UV regulators of these cross sections. In this proceedings article, we highlight only one important feature of the algorithm, namely that the physical output is insensitive to these regulators. A complete description of the algorithm will be given in an upcoming publication.